DESENVOLVIMENTO E VALIDAÇÃO DE UM MÉTODO VOLTAMÉTRICO APLICADO NA DETERMINAÇÃO DE DOPAMINA - Santos, Rafaella Ribeiro dos (2021)
Dopamine is a neurotransmitter that performs important functions in the human body and its presence at abnormal levels of concentration in the human body, can cause diseases such as parkinson and schizophrenia. Therefore, this molecule must be determined in biological fluids. In this work, a methodology was developed, based on differential pulse voltammetry, using a sensor built by a printed electrode, modified with Carbon Black. The results obtained with cyclic voltammetry (CV) showed that there was an improvement in the sensitivity of the sensor after modification of the electrode and from the application of the t-test, a significant difference existed between the values of the magnitudes of the peak currents (Ip) before and after the modification. Through the cyclic voltammetry performed in the study of the scan rate, it was verified that the electron transfer process of the dopamine in the sensor is controlled by diffusion. Afterwards, the conditions of the electroanalytical method were optimized, and the method was then developed in 0.1 mol L-1 phosphate buffer electrolyte, at pH 6.0, by differential pulse voltammetry with 0.04s modulation time, amplitude of 50 mV and scan rate of 3.0 mVs-1. The method was then validated in order to confirm its reliability, for application in urine samples. For this, linearity parameters, detection limits (LD), quantification limits (LQ), accuracy, precision and selectivity were evaluated, applying different statistical tests. The urine sample did not show a significant matrix effect, indicating that future measurements could be performed in pure electrolyte. The linear working range adopted was 2.0 to 11.0 μmol L-1 and the linearity was adequate, with significant linear regression and lack of non-significant adjustment, at a 95% confidence level, observed by application of the F-tests. Still, the analyzes of the graphs of residues and tests of Cochran showed the homecedasticity of the variances. The detection and quantification limits obtained were 0.42 μmol L-1 and 1.28 μmol L-1, respectively. The method proved to be selective for uric acid, ascorbic acid and paracetamol as long as its concentration is three times below the dopamine value. The precision of the method was estimated in terms of repeatability and intermediate precision, where both were shown appropriate, with a relative standard deviation in the range of 0.94 to 2.89%. The recovery rates performed in the urine sample proved to be adequate and varied between 94 and 106.3%. Thus, it is suggested that the electroanalytical methodology developed can be applied in the determination of Dopamine, presenting advantages compared to traditional methods of analysis, such as low cost, speed and reduction in the use of reagents.